Membangun Kedaulatan Pangan Melalui Sekolah Lapang Agroekologi dengan Bertani Ramah Lingkungan - Rahmi Awalina; Delvi Yanti; Syaifuddin Islami (Warta Pengabdian Andalas, 2021)
The concept of food sovereignty has officially become the goal and approach in national food development, as stated in Law no. 18 of 2012 concerning Food, food independence and food security. This activity aimed to provide an overview of the concept of food sovereignty that the community can carry out through the Agroecology Field School. The results from the field school show that food sovereignty was an essential strategy to complement food security as the ultimate goal of food development so that people can be independent without any dependence. Agroecology field school activities emphasize that food sovereignty relates to farmers' rights and access to all agricultural resources, including land, water, production facilities, technology, marketing, and consumption. This condition can be measured at various levels at the individual, household, community and regional levels. The agroecology field school activities were held in two locations: Lubuk Gadang Selatan and Sako Utara Pasia Talang, West Sumatra. The material presented at the extension activity includes Introduction to Agricultural Science, Agroecology, Basics of Agricultural Ecosystems, Food Sovereignty, Cultivation and Breeding Techniques, Plant Maintenance, Fundamentals of Soil Science, Irrigation Management, Plant Breeding and Post Harvest.